2022
DOI: 10.3390/cells11142178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toxic AGEs (TAGE) on Human Health

Abstract: The habitual and excessive consumption of sugar (i.e., sucrose and high-fructose corn syrup, HFCS) is associated with the onset and progression of lifestyle-related diseases (LSRD). Advanced glycation end-products (AGEs) have recently been the focus of research on the factors contributing to LSRD. Approaches that inhibit the effects of AGEs may be used to prevent and/or treat LSRD; however, since the structures of AGEs vary depending on the type of reducing sugars or carbonyl compounds to which they respond, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 122 publications
0
33
0
Order By: Relevance
“…Enhanced intake of sugars, in particular fructose along with abundant AGE-rich diet are associated with the formation of intracellular AGEs which cause induction of lipogenesis in addition to inflammation in crosstalk with ER stress [118]. Apart from the extravasation of AGEs as well as their crosstalk with RAGE has a correlation with formation besides evolution of different chronic diseases inclusive of steatosis along with CVD [119]. A correlation amongst escalated quantities of different kinds of AGEs along with NAFLD was illustrated in a recent meta-analysis [120].…”
Section: Atherogenic/cardiovascular Disease (Cvd) Along With Er Stres...mentioning
confidence: 99%
“…Enhanced intake of sugars, in particular fructose along with abundant AGE-rich diet are associated with the formation of intracellular AGEs which cause induction of lipogenesis in addition to inflammation in crosstalk with ER stress [118]. Apart from the extravasation of AGEs as well as their crosstalk with RAGE has a correlation with formation besides evolution of different chronic diseases inclusive of steatosis along with CVD [119]. A correlation amongst escalated quantities of different kinds of AGEs along with NAFLD was illustrated in a recent meta-analysis [120].…”
Section: Atherogenic/cardiovascular Disease (Cvd) Along With Er Stres...mentioning
confidence: 99%
“…During the last century, several advanced glycation end-products (AGEs) have been identified and studied [1,2]. Many AGEs are produced in certain organs and tissues and circulate in the body through the bloodstream, whereas dietary AGEs are taken up by the body through food and drink consumption [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings showed that intracellular TAGE damaged not only liver cells [ 9 , 10 , 11 , 12 ], but also other cell types, including neuroblasts, pancreatic cancer cells, cardiomyocytes, myoblasts, pancreatic islet β-cells, osteoblasts, and cardiac fibroblasts [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The leakage of cytotoxic intracellular TAGE into the blood has been suggested to increase their concentration in circulating fluids [ 20 , 21 , 22 ]. Extracellular TAGE and receptor for AGEs (RAGE) interactions were found to affect intracellular signaling, gene expression, and the release of pro-inflammatory molecules and promoted reactive oxygen species (ROS) production in many cell types [ 23 , 24 , 25 , 26 , 27 ], and these changes collectively contribute to the development of NASH.…”
Section: Introductionmentioning
confidence: 99%